MATA KULIAH BUSINESS ENGLISH SEBAGAI PENUNJANG KARIR MAHASISWA MANAJEMEN DAKWAH - Ela Rosyida (Program Studi Manajemen Dakwah, Fakultas Dakwah, Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
The Business English course has a crucial role in supporting the careers of Da'wah Management students. This article explains how the ability to communicate in English and an understanding of global business aspects can equip students with the skills necessary to succeed in their careers. By mastering Business English, students can bridge the communication gap between cultures, optimize international job opportunities, and increase competitiveness in an industry that is increasingly connected globally.